From enemy territory Pale diary, 5 April to 15 July 1992 - Vuksanović, Mladen 1942- (Saqi in association with the Bosnian Institute, 2004)
Set at the outbreak of the war in Bosnia, this diary, penned by the award-winning journalist Vuksanovic, records the extraordinary unfolding of events. The author lived in the ski resort of Pale, 15km above Sarajevo. In April 1992, when Radovan Karadzic launches his savage assault on the city. Vuksanoviae - refusing to collaborate - becomes a prisoner in his own home, cut off from his children and friends below. He expressed his terror and disgust within these pages. During that time, he describes in chilling detail not only the horrifying war - with the looting, ethnic cleansing and betrayal that became commonplace - but also the mental strain of war on the individual. He and his wife finally managed to escape in a UN refugee bus via Hungary to Croatia, smuggling with them these notes from enemy territory